Strategi dan Implementasi Keberlanjutan PT Garuda Indonesia dalam Mewujudkan ESG - Annisa Trimur Fadila; Ida Bagus Ketut Bayangkara (Pusat Riset dan Inovasi Nasional, 2025)
This paper explores the ESG (Environmental, Social, and Governance) strategy adopted by PT Garuda Indonesia following its restructuring phase, with reference to the GRI Standards 2021 and SDG Compass framework. Initiated in 2020, the restructuring was a strategic response to the escalating financial and operational challenges exacerbated by the COVID-19 pandemic. As part of its recovery strategy, Garuda Indonesia has embraced ESG as a foundational approach to promote long-term sustainability and contribute to the realization of the Sustainable Development Goals (SDGs). Employing a qualitative-descriptive method, the study analyzes the company’s 2023 Sustainability Report. The findings reveal that the airline has demonstrated a tangible commitment to lowering carbon emissions, enhancing employee well-being, and reinforcing governance structures. Nonetheless, there remains a need for greater transparency in reporting and better integration of ESG metrics into the company’s core operations. The study suggests that Garuda Indonesia should enhance the alignment of its ESG initiatives with SDG indicators and adopt the GRI Standards in a more holistic manner.